Iranian teacher's code-switching practices in an English as a foreign language classroom - Balouchi, Shima (2011)
Code-switching is an alternate use of two or more languages in the same utterance or conversation. The lack of adequate proficiency in the practice of code-switching among the teachers of English language becomes a central issue in code-switching implementation in Iran. Questions are raised on how teachers used the exclusion of code-switching from the classroom in teaching the English language. The main purpose of this thesis is to investigate and examine closely the functions of code-switching in a very limited and defined classroom and some of the motivations behind this usage. This study adopted a qualitative approach with some quantification of data in terms of frequency. The code-switching examples were analysed in their discourse contexts. Conversational analysis was selected as the methodology for this study. Based on different studies conducted, it is found that the conversational analysis can be usefully applied in the study of classroom language code-switching. This study is based on observations, audio recordings and teacher interviews of five English as a foreign language (EFL) classroom. The participants were selected based on purposive sampling. The observations and interviews from the classrooms were transcribed verbatim and analyzed manually. The findings indicated that the teacher selected for this research practices code-switching more frequently when teaching grammar, give instructions and make vocabulary translation. It is found that the use of code-switching by the teacher is highly ordered. It is also found that the use of code-switching in the teacher’s utterances is first and foremost to facilitate the foreign language learning and ensure understanding of the lesson among the students. In conclusion, the observed patterns suggested that code-switching in English as a foreign language classroom has a pedagogical purpose, and it serves as a valuable instrument in English language teaching. The findings of this study might illuminate practitioners of EFL regarding the roles of code-switching in the classrooms as well as to raise their awareness of the benefits of code-switching in classrooms. These results revealed that code-switching can be a highly recommendable language strategy in foreign language classrooms.